MANAJEMEN PRIVASI PEMAIN KOREAN ROLEPLAY PADA PENGUNGKAPAN IDENTITAS DI TELEGRAM - Arif, Orchida Lutfiyah Smarta; Mustika Chairil, Augustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe the privacy management process of Korean Roleplay (KRP) players in identity disclosure on Telegram using Sandra Petronio’s Communication Privacy Management (CPM) theory. Employing a qualitative approach with a virtual ethnography method, this research explored how KRP players establish privacy boundaries and manage personal information within an anonymous online community. Data were collected through participant observation, in-depth interviews with twelve informants, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings reveal that KRP players actively manage privacy by selectively disclosing personal information based on interpersonal trust, relationship closeness, and individually established privacy rules. Identity disclosure occurs gradually after careful consideration of communication partners and potential risks. Participants also continuously negotiate privacy boundaries to respond to threats such as doxing, stalking, identity misuse, and unauthorized dissemination of personal information. The study concludes that privacy management among Korean Roleplay players is a dynamic process influenced by trust, previous experiences, and perceived communication risks. These findings contribute to the development of Communication Privacy Management studies in anonymous virtual communities and provide practical insights into digital privacy protection in online communication environments. Keywords: Communication Privacy Management, Korean Roleplay, Identity Disclosure, Privacy Management, Telegram